(untitled) (Prithvi Journal of Research and Innovation, 2025)
The demand for blood and its components is constantly rising around the globe. Unlike in developed regions, recruiting donors to collect sufficient amount of blood regularly on non-paid and voluntary basis is a challenging activity in less developed countries like Nepal. Low donation rates, limited awareness, various perceived barriers and misconceptions are likely contributing factors to this public health concern. Therefore, this paper explores the knowledge, attitude, and practice of university students toward voluntary blood donation in Pokhara and examines the factors influencing their participation in blood donation. The cross-sectional quantitative study was conducted among 424 college students admitted to different academic programs. Approximately one-fourth had adequate knowledge on blood donation, but nearly two-thirds had favorable attitude. Only one in five participants had ever donated blood. Among blood donors, about one-half participants donated only once until the survey date. Male students who were 22 years or older, studying at Master’s level and had good knowledge about blood donation were more likely to have donated blood. The findings of the study concluded that students at early adolescence, including female students, should be motivated through tailored awareness and educational programs to improve participation in voluntary blood donation.